Design considerations and operational performance of anaerobic digester: A review. Issue 1 (31st December 2016) - Mir, Muzaffar Ahmad; Hussain, Athar; Verma, Chanchal
Abstract: Due to the decline in fossil fuel reservoirs, the researchers emphasized more on the production of biogas from organic waste. Producing the renewable energy from biodegradable waste helps to overcome the energy crisis and solid waste management, which is done by anaerobic digestion. Anaerobic digestion is the controlled breakdown of organic matter into methane gas (60%), carbon dioxide (40%), trace components along with digested used as soil conditioner. However, there is vast dearth of literature regarding the design considerations. The batch digestion system yields a cost-effective and economically viable means for conversion of the food waste to useful energy. It is therefore recommended that such process can be increasingly employed in order to get and simultaneously protect the environment. This paper aims to draw key analysis and concern about the design considerations, analysis of gas production, substrates and inoculua utilization, uses and impacts of biogas.